Biology and management of termites in field and fruit crops - Kumari, Suman; Kaur, Prabhjot; Singh, Harinder (Indian Farming, 2024)
Termites are very significant pest of important field and fruit crops. These are found in a wide range of terrestrial environments and distributed throughout the tropical, subtropical and temperate regions of the world. It infests the plants in reproductive and vegetative stages. Termites usually are greyish-white creatures that belongs to order Isoptera, having cryptic habits and incompletemetamorphosis. Over 70% of all the termite species belongs to Termitidae family that seriously damages both agricultural and horticultural crops. Odontotermes obesus and Microtermes obesi are the two major species causing damage to plants in the vegetative or reproductive stages, especially wheat, maize, barley, pulses, oilseeds, vegetables, fruits, plantations, sugarcane, cotton,etc. Sometimes, crop yields are severely lowered due to the inability to make up losses incurred at or close to maturity. Such losses jeopardize marginal farmers' livelihoods and impair food security. Therefore, it is imperative to understand the biology as well as management of termites to save the financial and yield losses caused by them.